UPAYA PEMBERDAYAAN EKONOMI PEREMPUAN MELALUI PENGEMBANGAN MANAJEMEN USAHA KECIL (Studi diskriptif pada Kegiatan Usaha Kecil Ibu-ibu Desa Wirolegi Kabupaten Jember, Dampingan Pusat Studi Wanita UM Jember) - Retno Endah Supeni; Maheni Ika Sari (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2011)
Economic empowerment of women that lead by Women Studies Center Muhammadiyah of Jember University inWirolegi, one of the center of poverty in Jember, still has many works to do concerned with elements ofeconomic empowerment of women to improve these women’s economy welfare. The purpose of this study is tocapture needs of their small business and as the result is a development model of small business management .It will help them to get access to economy sources, to reach the same position, to have markets, finance andbusiness skill to improve the growth of their own business. This study uses qualitative model with focus groupdiscussion and depth interview.